2018
DOI: 10.11648/j.wjap.20180301.12
|View full text |Cite
|
Sign up to set email alerts
|

±Water: Demonstration of Water Properties, Depending on its Electrical Potential

Abstract: The aim of this work is to demonstrate that the physicochemical properties of water depend on its electric charge (potential). It is also shown that the physico-chemical properties of aqueous solutions depend very much on the electric charge (potential) of the water on which these solutions are prepared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 7 publications
0
39
0
Order By: Relevance
“…It was previously shown that the shape of crystals formed after evaporation of chloride solutions depends on the sign of the electric potential of water used to prepare such solutions. In particular, it was shown that the evaporation of chloride solutions prepared in water with a negative electric potential is accompanied by the formation of tree-like crystals (Figure 3) [17][18][19][20][21]. Based on this, it was concluded that low-frequency PEMFs cause negative electrification of aqueous solutions of chlorides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously shown that the shape of crystals formed after evaporation of chloride solutions depends on the sign of the electric potential of water used to prepare such solutions. In particular, it was shown that the evaporation of chloride solutions prepared in water with a negative electric potential is accompanied by the formation of tree-like crystals (Figure 3) [17][18][19][20][21]. Based on this, it was concluded that low-frequency PEMFs cause negative electrification of aqueous solutions of chlorides.…”
Section: Discussionmentioning
confidence: 99%
“…To find out the physicochemical basis of the regenerative effects of low-frequency PEMFs on the nervous system, we studied their effect on the crystallization of chlorides, which are the main inorganic anions, both in the cytoplasm of neurons and in their environment. At the same time, we took into account the characteristic ability of chlorides to form tree-like crystals in environments with a negative electric potential [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…. It is a copper powder located near the boundary of waters with positive (above the line) and negative (below the line) potentials [2,3].…”
Section: Aimmentioning
confidence: 99%
“…It has been particularly shown that the evaporation of salt solutions with positive electric potential is accompanied by the formation of cubic crystals and the evaporation of salt solutions with negative electric potential is accompanied by the formation of needle-like crystals ( fig. 1, 2) [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation